Mass Transfer and Chemical Reaction Approach of the Kinetics of the Acetylation of Gadung Flour using Glacial Acetic Acid - Andri Cahyo Kumoro; Rizka Amalia (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2015)
Acetylation is one of the common methods of modifying starch properties by introducing acetil (CH3CO) groups to starch molecules at low temperatures. While most acetylation is conducted using starch as anhidroglucose source and acetic anhydride or vinyl acetate as nucleophilic agents, this work employ reactants, namely flour and glacial acetic acid. The purpose of this work are to study the effect of pH reaction and GAA/GF mass ratio on the rate of acetylation reaction and to determine its rate constants. The acetylation of gadung flour with glacial acetic acid in the presence of sodium hydroxide as a homogenous catalyst was studied at ambient temperature with pH ranging from 8-10 and different mass ratio of acetic acid : gadung flour (1:3; 1:4; and 1:5). It was found that increasing pH, lead to increase the degree of substitution, while increasing GAA/GF mass ratio caused such decreases in the degree of substitution, due to the hydrolysis of the acetylated starch. The desired starch acetylation reaction is accompanied by undesirable hydrolysis reaction of the acetylated starch after 40-50 minutes reaction time. Investigation of kinetics of the reaction observed that the value of mass transfer rate constant (Kcs) is smaller than the surface reaction rate constant (k). Thus, it can be concluded that rate controlling step is mass transfer. © 2015 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)